(untitled) (Kobe, 1988)
Focused on the relationships between innovation and organizational management; research findings were presented and compared from an internaional perspective, and their theoretical and practical implications were disscused
Keywords: Technological innovations,Đổi mới công nghệ,Quản trị sản xuất công nghiệp,Industrial management; Nhật Bản,Japan